PENERAPAN SIX SIGMA DALAM UPAYA PENURUAN ADUAN BRT TRANS JATENG KORIDOR 7 - Yunita Primasanti; Bekti Nugrahadi; Indah Wahyu (ITB AAS Indonesia Surakarta, 2025)
Improving the quality of public transportation services is a crucial factor in maintaining public satisfaction and trust. Trans Jateng's BRT, particularly on corridor 7, continues to face challenges in the form of a high number of passenger complaints related to delays, comfort, and other operational aspects. This study aims to apply a Six Sigma approach to reduce the number of complaints while improving service quality. The research methodology uses the DMAIC (Define, Measure, Analyze, Improve, Control) framework, collecting data through passenger complaint documentation, field observations, and interviews with management and operators. The results indicate that the highest complaint categories relate to punctuality and fleet condition, with an initial sigma value at a low level. Through root cause analysis, improvement priorities were established, including improving fleet maintenance schedules, bus crew training, and optimizing the trip monitoring system. The implementation of corrective actions significantly reduced the number of complaints during the trial period, resulting in an improvement in the sigma level. This study's contribution lies in the systematic application of Six Sigma in the public transportation sector, a rarely studied area, and provides practical recommendations for Trans Jateng BRT management in sustainably managing service quality. The conclusion of this study is that Six Sigma is proven to be effective as a quality management method to reduce customer complaints and increase the reliability of bus rapid transit services. Improving the quality of public transportation services is a crucial factor in maintaining public satisfaction and trust. Trans Jateng's BRT, particularly on corridor 7, continues to face challenges in the form of a high number of passenger complaints related to delays, comfort, and other operational aspects. This study aims to apply a Six Sigma approach to reduce the number of complaints while improving service quality. The research methodology uses the DMAIC (Define, Measure, Analyze, Improve, Control) framework, collecting data through passenger complaint documentation, field observations, and interviews with management and operators. The results indicate that the highest complaint categories relate to punctuality and fleet condition, with an initial sigma value at a low level. Through root cause analysis, improvement priorities were established, including improving fleet maintenance schedules, bus crew training, and optimizing the trip monitoring system. The implementation of corrective actions significantly reduced the number of complaints during the trial period, resulting in an improvement in the sigma level. This study's contribution lies in the systematic application of Six Sigma in the public transportation sector, a rarely studied area, and provides practical recommendations for Trans Jateng BRT management in sustainably managing service quality. The conclusion of this study is that Six Sigma is proven to be effective as a quality management method to reduce customer complaints and increase the reliability of bus rapid transit services.